2004
DOI: 10.1385/endo:23:1:17
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamines Are Unlikely to Function as a Nutrient-Sensor in 3T3-L1 Adipocytes: A Comparison of UDP-Hexosamine Levels after Increased Glucose Flux and Glucosamine Treatment

Abstract: Whether the hexosamine biosynthesis pathway acts as a nutrient-sensing pathway is still unclear. Glucose is directed into this pathway by GFAT. Because the activity of GFAT is tightly regulated, we examined whether UDP-hexosamine levels can increase significantly and dose-dependently in response to elevated glucose concentrations. In glucosamine-treated 3T3-L1 adipocytes, inhibition of insulin-stimulated glucose uptake was highly correlated with UDP-hexosamine levels (r = -0.992; p < 0.0001 for UDP-GlcNAc and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Perturbation of the HBP causes diabetes in murine models 33 and in 3T3-L1 adipocytes; insulin-stimulated glucose uptake results in 30% increase in the production of UDP-GlcNAc. 34 Of special interest, development of insulin resistance is associated with a fourfold increase in the levels of UDP-GlcNAc in the skeletal muscles, 35 whereas we observed that inhibition of UAP1 expression results in a significant decrease in the levels of UDP-GlcNAc (Figure 2e). High-glucose-induced development of insulin resistance can be prevented by an inhibitor of GFPT1, 33 and it remains to be determined whether UAP1 could be pharmacologically regulated to affect insulin responsiveness.…”
Section: Resultsmentioning
confidence: 70%
“…Perturbation of the HBP causes diabetes in murine models 33 and in 3T3-L1 adipocytes; insulin-stimulated glucose uptake results in 30% increase in the production of UDP-GlcNAc. 34 Of special interest, development of insulin resistance is associated with a fourfold increase in the levels of UDP-GlcNAc in the skeletal muscles, 35 whereas we observed that inhibition of UAP1 expression results in a significant decrease in the levels of UDP-GlcNAc (Figure 2e). High-glucose-induced development of insulin resistance can be prevented by an inhibitor of GFPT1, 33 and it remains to be determined whether UAP1 could be pharmacologically regulated to affect insulin responsiveness.…”
Section: Resultsmentioning
confidence: 70%
“…OGT is proposed to respond directly to UDP-GlcNAc levels (via mechanisms discussed in the section on Protein Glycosylation), and the responsiveness of the HBP pathway to glucose is thought to be an important component of OGT's cellular biochemistry. The responsiveness of the pathway was challenged, however, on the basis of measurements showing that total cellular UDP-GlcNAc levels vary only twofold in response to a physiologically relevant range of extracellular glucose concentrations (between 1 and 25 mM) (55). These measurements were of total cellular UDP-GlcNAc levels, and it is possible that a larger dynamic range would be observed in the cytosol and/or nucleus.…”
Section: The Hexosamine Biosynthetic Pathwaymentioning
confidence: 99%
“…Intuitively, increased cellular glucose and flux through the HBP would only increase UDP-GlcNAc levels to a specific concentration and no higher. For example, adipocytes exposed to increasing amounts of glucose in the presence of insulin show a 30% increase in UDP-GlcNAc concentration compared to a 365% increase in glucose uptake13. Is this slight increase in UDP-GlcNAc concentration enough to allow O-GlcNAc to act as a nutrient sensor?…”
Section: Nutrient Flux Through the Hexosamine Biosynthetic Pathway (Hbp)mentioning
confidence: 99%